2016
DOI: 10.1007/s40069-016-0128-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Strength–Maturity Models Accounting for Hydration Heat in Massive Walls

Abstract: The objective of this study was to evaluate the capability of different strength-maturity models to account for the effect of the hydration heat on the in-place strength development of high-strength concrete specifically developed for nuclear facility structures under various ambient curing temperatures. To simulate the primary containment-vessel of a nuclear reactor, three 1200-mm-thick wall specimens were prepared and stored under isothermal conditions of approximately 5°C (cold temperature), 20°C (reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…This agrees with the observations made by other researchers (Tank and Carino 1991;Yi et al 2005;Liao et al 2008;Kwon et al 2014). Values of E tabulated in Case I in Table 3 show linearly decreasing tendency with increase in T max for all concrete strengths, which agrees with the experimental observations made by Jonasson et al (1995), Kim et al (2001) and Yang et al (2016). It can also be observed that E decreases with increase in f 0 cd (or with decrease in W/C) at a given T max , which was also in agreement with previous observations made by Kim et al (2001), Abdel-Jawad (2006) and Kwon et al (2014).…”
Section: An Empirical Model For the Development Of Compressive Strengsupporting
confidence: 92%
“…This agrees with the observations made by other researchers (Tank and Carino 1991;Yi et al 2005;Liao et al 2008;Kwon et al 2014). Values of E tabulated in Case I in Table 3 show linearly decreasing tendency with increase in T max for all concrete strengths, which agrees with the experimental observations made by Jonasson et al (1995), Kim et al (2001) and Yang et al (2016). It can also be observed that E decreases with increase in f 0 cd (or with decrease in W/C) at a given T max , which was also in agreement with previous observations made by Kim et al (2001), Abdel-Jawad (2006) and Kwon et al (2014).…”
Section: An Empirical Model For the Development Of Compressive Strengsupporting
confidence: 92%
“…Whereas Yi et al (2005) observed that S u depends mainly on curing temperature, Kwon et al (2014) and Liao et al (2008) suggested S u as a function of temperature and humidity after their experimental observations. ''Activation energy has been proposed as a function of temperature T c by Freiesleben and Pedersen (1977) and Jonasson et al (1995), T c and t by Kim et al (2001), the chemical components of the cementitious materials and Blaine value by Schindler (2004) and Poole (2006), the water-cement ratio (W/C), T c , and degree of hydration by Abdel-Jawad (2006), and T c and concrete age by Yang et al (2016). Frequency factor was suggested as a function of both T c and humidity by Liao et al (2008) and a function of humidity only by Kwon et al (2014).…”
Section: Development Of Concrete Compressive Strengthmentioning
confidence: 99%
“…However, real-time monitoring of concrete strength using non-destructive methods is still a big challenge and a major source of uncertainty. In this context, maturity methods for in situ estimation of concrete strength, based solely on temperature, have been widely used [12][13][14][15] and many commercial solutions have been developed. But these might not always be the most accurate, as the maturity and related compressive strength are also influenced by concrete mixture and the weather (as reported by Yang et al [12], differences of up to 30% between estimated and real strength could be obtained when using maturity methods for certain types of cement and curing conditions).…”
Section: Introductionmentioning
confidence: 99%